Cultural diplomacy and co-operation in ASEAN: The role of arts and culture festivals - OCON, David (Institutional Knowledge at Singapore Management University, 2021)
Beyond their traditional role as entertainment, form of expression and meeting spaces within local communities, arts and culture festivals can perform various functions. They can serve as showcases of artistic pride, signal openness towards cultural diversity, support the local economy, contribute to reducing political tension and provide grounds to consolidate international relationships. On occasion, such festivals function as tools to support the vision of a multilateral co-operation institution, as is the case of the Association of Southeast Asian Nations (ASEAN). Through a comprehensive review of the arts and culture festivals curated in ASEAN, this article investigates the festivals’ ulterior motivations. A range of economic, political, diplomatic, and organisational logics explain the evolution of such festivals during the last fifty years. The article concludes that arts and culture festivals have remained a compelling and instrumental co-operation mechanism in ASEAN, but formats and approaches need substantial revision.